The spotty holiday - Rippin, Sally (Hardie Grant Egmont, 2011)
Billie has lots of fun things planned for her visit to Grandma's. But when Billie wakes up covered in spots, will her holiday be ruined?
Keywords: Vacations / Juvenile fiction; Chickenpox / Juvenile fiction; Großmutter; Schulferien; Mädchen; Windpocken; Besuch; Kinderbuch